In Vitro and In Vivo Effects of Synthesis Novel Phenoxyacetamide Derivatives as Potent Apoptotic Inducer against HepG2 Cells through PARP-1 Inhibition - Mai M. Sayed; Zohour I. Nabil; Nahla S. El-Shenawy; Rasha A. Al-Eisa; Mohamed S. Nafie (MDPI AG, 2023)
To discover potential cytotoxic agents, new semi-synthetic phenoxy acetamide derivatives, compound I and compound II, were synthesized, characterized, and screened for their cytotoxic activity against breast cancer (MCF-7) and liver cancer (HepG2) cell lines. The two compounds were more promising against HepG2 than the MCF-7 cell line according to IC50 values. When tested against the HepG2 cell line, compound I, and compound II both had significantly increased cytotoxic activity when compared to the reference medication 5-Fluorouracil (5-FU), with IC50 values of 1.43 M, 5.32 M, and 6.52 M for compound 1, 5-FU and compound II, respectively. Also, compound I displayed a degree of selectivity towards cancer cells compared to normal cells. Compound I significantly enhanced HepG2 total apoptotic cell death by about a 24.51-fold increase. According to cell cycle analysis, compound I induced the arrest of the cell cycle phases G1/S and blocked the progression of the HepG2 cells. Applying the RT-PCR technique achieved a highly significant upregulation in pro-apoptotic genes. The anti-apoptotic gene was significantly downregulated. There was an intrinsic and extrinsic pathway, but the intrinsic pathway was the dominant one. Tumor growth suppression as measured by tumor weight and volume and other hematological, biochemical, and histopathological analyses confirmed the efficacy of compound I as an anticancer agent in vivo examination. Finally, the molecular docking study revealed that compound I was properly docked inside the binding site of PARP-1 protein with stable binding energies and interactive binding modes. Therefore, compound I shows promise as a selective anti-cancer derivative for the treatment of liver cancer after more investigations and clinical studies. This selectivity is a favorable characteristic in the developing cytotoxic agents for cancer treatment, as it indicates a potential for reduced harm to health tissues.